A new 3-D coordination polymer as a precursor for CuI-based thermoelectric composites. Issue 45 (7th November 2018) - Bai, Shi-Qiang; Wong, Ivy Hoi Ka; Zhang, Nan; Lin Ke, Karen; Lin, Ming; Young, David James; Hor, T. S. Andy
Abstract : A room temperature stable CuI-coordination polymer was characterized and pyrolysed to form a low density, thermoelectric composite with a relatively high Seebeck coefficient (∼1308 μV K −1 ) below 100 °C. Abstract : Two complexes, [Cu6 I6 (L1)3 ] n (I ) and [Cu4 I4 (L2)2 ] n (II ) (L1 = 1, 4-bis(phenylthio)but-2-yne; L2 = 1, 4-bis(phenylthio)butane), as precursors for thermoelectric composites were prepared using a literature procedure. During the preparation of I, an unexpected 3-D polymorph [Cu4 I4 (L1)2 ] n (1 ) with a triclinic space group and an infinite [CuI] n staircase structure was obtained. This new polymorph (1 ) exhibited the same structure at both room temperature and 173 K. Complexes 1 and II were therefore pyrolysed to composites 2 and 3, respectively, at 400 °C under a nitrogen gas flow. Composite 3 was pale in color with a low carbon content (0.05 wt%) and easily disassembled during handling. By comparison, the high carbon containing (10.2 wt%) composite 2 can be compressed into a robust, light pellet (density 3.58 g cm −3 ), which showed a moderate to high Seebeck coefficient (543–1308 μV K −1 ) over the temperature range 70–240 °C.